The theory of subjectivity in the study of chemical dependency: reflecting about existing theories and practices - Melo Caixeta, Thamiris; Deusdará Mori, Valéria; Santos Bezerra, Marília (Revista Pesquisas e Práticas Psicossociais, 2017)
The topic related to chemical dependence has been increasingly approached in studies of professionals from different areas. From its theoretical models to professional practice models, the use of chemical substances has generated questions that reflect the need to create new modes of intelligibility of the theme. The present work, using the constructive-interpretative method that is based on Qualitative Epistemology (González Rey, 1997, 2005b), presents a reflection about the theme, emphasizing the production of social subjectivity, individual subjectivity and processes related to health in the context of the clinical dependency. For this, a case study was carried out, where the production of knowledge values the singular and the dialogical, during the process of information construction. Keywords: Chemical Dependency. Subjectivity. Health.